2022
DOI: 10.21037/tcr-22-1428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bronchial methylene blue staining and modified inflation-deflation method in identifying the intersegmental plane during lung segmentectomy

Abstract: Background: Identification of the intersegmental plane (ISP) is the critical step in lung segmentectomy because of the complicated anatomic variations. Bronchial methylene blue staining was developed by our team in 2015 and is now commonly used at our center, it could rapidly and accurately identify the ISP. In this study, we aimed to compare bronchial methylene blue staining with the modified inflation-deflation method in terms of their perioperative characteristics and to present our experience of the methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Wang and colleagues explored an exciting approach to integrate these goals with the use of methylene blue dye marking to shorten operative time as compared to inflation-deflation technique (1). Similarly, our group would like to highlight the opportunity to employ navigational bronchoscopy to achieve similar goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and colleagues explored an exciting approach to integrate these goals with the use of methylene blue dye marking to shorten operative time as compared to inflation-deflation technique (1). Similarly, our group would like to highlight the opportunity to employ navigational bronchoscopy to achieve similar goals.…”
Section: Discussionmentioning
confidence: 99%
“…We read the recently published article, "Comparison of bronchial methylene blue staining and modified inflationdeflation method in identifying the intersegmental plane during lung segmentectomy," by Wang and colleagues with great interest (1). We congratulate the authors on this successful submission on an emerging topic and appreciate the opportunity to offer a few comments.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Wang and colleagues have reported regarding this issue. They compared between the bronchial methylene blue staining method as a transbronchial method and the modified inflation-deflation method as a transvascular method (13). They retrospectively reviewed 62 patients underwent bronchial methylene blue staining, and 50 patients underwent the modified inflation-deflation method.…”
mentioning
confidence: 99%